Social Framing Effects in Leadership: Preferences or Beliefs? - Edward Cartwright; Michalis Drouvelis (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We experimentally study the impact of framing effects in a repeated sequential social dilemma game. Our between-subjects design consists of two group level ("Wall Street" vs. "Community") and two individual level ("First (Second) Movers" vs. "Leaders (Followers)") frames. We find that average contributions are significantly higher when the game is called the Wall Street game than when it is called the Community game. However, the social framing effect disappears when we control for players' first-order and second-order beliefs. Overall, our evidence indicates that social frames enter people's beliefs rather than their preferences.
Keywords: H41; C72; C92; 330; framing; public good; experiment; beliefs